Environmental quality intervention for waste disposal in the community in Kalinaun Village, East Likupang District - Maddusa, Sri Seprianto; Asrifuddin, Afnal; Kawatu, Paul A. T.; Kapugu, Avinia; Nasira, Azmi; Tamon, Cecilya (Sociality: Journal of Public Health Service, 2024)
Waste processing in various villages has not been good and there is a accumulation of garbage so that it can spoil the scenery / aesthetics of the environment and cause the spread of disease. This service activity aims to provide knowledge and understanding to the community of Environment V and VI of Kalinaun Village, East Likupang District regarding Waste Management through counselling and making fertilizer from organic waste. The method of counselling and making organic fertilizer is a method carried out in solving the problem of waste in Kalinaun village in guard V and Vl of East Likupang district. Before counselling is carried out, the community fills out the Pre-test first and post-test after counselling. There were 22 respondents in counselling, before counselling 10 respondents with good knowledge categories became 14 respondents after counselling. Continuous monitoring efforts from community leaders need to be carried out to monitor success in community-based waste management.